Light-induced control of the spin distribution on Cu–dithiolene complexes: A correlated ab initio study (2019)
Metal dithiolene complexes—M(dmit)2—are key building blocks for magnetic, conducting, and optical molecular materials, with singular electronic structures resulting from the mixing of the metal and dmit ligand orbitals. Their use in the design of magnetic and conducting materials is linked to the control of the unpaired electrons and their localized/delocalized nature. It has been recently found that UV–Vis light can control the spin distribution of some [Cu(dmit)2]−2 salts in a direct and reversible way. In this work, we study the optical response of these salts and the origin of the differences observed in the EPR spectra under UV–Vis irradiation by means of wave function-based quantum chemistry methods. The low-lying states of the complex have been characterized and the electronic transitions with a non-negligible oscillator strength have been identified. The population of the corresponding excited states promoted by the UV–Vis absorption produces significant changes in the spin distribution, and could explain the changes observed in the system upon illumination. The interaction between neighbor [Cu(dmit)2]−2 complexes is weakly ferromagnetic, consistent with the relative orientation of the magnetic orbitals and the crystal packing, but in disagreement with previous assignments. Our results put in evidence the complex electronic structure of the [Cu(dmit)2]−2 radical and the relevance of a multideterminantal approach for an adequate analysis of their properties. © 2019 by the authors.